Pemberdayaan Kader Desa dan Tokoh Masyarakat dalam Implementasi Strategi Deteksi Dini Kasus Malnutrisi Anak Balita di Desa Bukit Karangasem - Adhi, K. T.; Utami, N. W. A.; Adnyana, I M. S. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi, 2016)
Results of the research in 2014 in Karangasem found cases of children under five wasting (12.5%) and stunting (31.2%). This data was different from the results in the recording of Posyandu that showed low cases of children suffering malnutrition. Cases of children under five are malnourished likened to an iceberg phenomenon will require discovery strategy malnourished children under five years with active case finding is very important to do. This is due to the low participation of the community to bring the child to the posyandu. The purpose of this activity is to improve the knowledge and skills of cadres in monitoring the growth and involve community leaders in early detection and referral of cases of malnutrition cases. This activity is a method of training or workshops. The activities carried out in the Bukit village District of Karangasem. A total of 25 (83.3%) cadres and 8 (61.5%) community leader (kadus) present. Based on pre- post test results showed that the effective training of cadres and also increase knowledge kadus in (p<0.001). Weighing coverage were increase 20%. This showed public awareness of the importance of monitoring the weight of children under five in Posyandu. Necessary provision of continuous information and appreciation to increased coverage and motivated cadre and kadus of early detection of cases of malnutrition in children under five.
Keywords: malnutrition, stunting, children under five, early detection, cadre